(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article examines the inter-community relations between the borderland population of Katsina, Maradi, and Zamfara in the Nigeria-Niger borderlands. Despite the demarcation of the Nigeria-Niger boundary by European powers, the historical, environmental, economic, social, and linguistic similarities have promoted and necessitated relationships between these border areas. This analysis focuses on the impacts of various activities undertaken by the border communities on the development of inter-communal relations.